A study on soil moisture under different land management practices across two rural municipalities in semi-arid region of Mustang, Nepal - Dhakal, Sandesh; Kandel, Saroj; Subedi, Rajan (Banko Janakari, 2024)
Soil moisture refers to the water amount present in the soil, which is a critical factor influencing plant growth, nutrient cycling, and groundwater recharge. Accurate information on soil moisture-level is crucial for water resource management, agriculture, land degradation, and ecosystem health assessment in semi-arid mountainous regions. Therefore, this study aims to assess average soil moisture under different land managements of the two rural municipalities (Thasang and Gharapjhong) of the Mustang Valley using remote sensing and a geospatial approach. Sentinel-1 and Sentinel-2 data were processed in Google Earth Engine to derive soil moisture using the modified Dubois and Topp's models. The key findings demonstrated that the spatial distribution of soil moisture ranged from 0.01 to 0.4 m3/m3 with cropland exhibiting the highest values (0.36 m3/m3). The correlation of the average soil moisture with the rainfall showed a strong positive correlation with the coefficient of determination (R2) of 0.94. The findings of this paper contributes for a better understanding of soil moisture dynamics of different land cover types of this study region. Further, research on the modeling of soil moisture based on in-situ field data and other influencing factors is recommended.